Training and Utilization of Geographic Information Systems at Rahmatullah Lempake Samarinda Islamic Boarding School - Stefano, Andrew; Endayani, Sri (P3KM Politeknik Pertanian Negeri Samarinda, 2024)
The application of Geographic Information System (GIS) technology in education is becoming increasingly vital for enhancing digital literacy and spatial analysis skills. Rahmatullah Lempake Islamic Boarding School in Samarinda is one of the educational institutions with significant potential to utilize this technology in supporting the management of its environment and local resources. The initiative aims to provide students with training in GIS, enhancing their knowledge and skills in spatial data management and geographic analysis. The training employed a combination of lectures, discussions, and practical sessions using GIS software. It was attended by students aged 12 to 15 and covered foundational topics, such as an introduction to GIS, mapping applications, and data analysis techniques. The results of this training demonstrated a notable improvement in the students' understanding and basic GIS skills, as well as increased awareness of the technology's potential applications in their local environment. The integration of GIS into the educational process offers significant benefits, particularly in enhancing students' technological literacy and spatial analysis capabilities, which can be applied to environmental management activities within the Islamic boarding school. In conclusion, the GIS training at Rahmatullah Lempake Islamic Boarding School has effectively developed the students' foundational skills in technology and geographic analysis, offering practical benefits for future resource management and environmental planning endeavors.